Integrasi Nilai-Nilai Fiqh Muamalah Kontemporer dalam Praktik Ekonomi Modern - Husaini, Muhammad (Al Fattah Ejournal Sma Al Muhammad Cepu, 2025)
The rapid development of modern economics often ignores the principles of justice and social welfare. In this context, the integration of fiqh muamalah values in modern economic practices, especially in the Islamic banking sector and other economic transactions, becomes very relevant. This research aims to examine how the values of fiqh muamalah can be applied in contemporary economic practices to create a fairer and more transparent economic system. The type of research used is descriptive qualitative research, with a literature study approach and in-depth interviews. The main data sources came from fiqh muamalah literature, Islamic banking reports, as well as interviews with Islamic banking practitioners and fiqh muamalah experts. The results show that the principles of fiqh muamalah, such as the prohibition of usury and the importance of clarity in contracts, can be effectively applied in the modern economic system, especially in Islamic banking. The implementation of profit-sharing system that replaces interest (riba) proves the success of fiqh muamalah in creating fairer and mutually beneficial economic transactions. Nonetheless, the biggest challenge lies in adapting these principles in the face of global economic dynamics and technological developments. This research provides new insights into the potential of fiqh muamalah as an alternative in a more equitable and sustainable economic system.